2018
DOI: 10.1177/1010428318776822
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific expression of amine oxidases in breast cancer metastases

Abstract: We aimed to evaluate the expression of amine oxidase-related proteins in metastatic breast cancer tissue and determine its clinical implication. A tissue microarray was constructed from a total of 126 metastatic breast tumors (31 bone metastases (24.6%), 36 brain metastases (28.6%), 11 liver metastases (8.7%), and 48 lung metastases (38.1%)). Immunohistochemical staining for amine oxidase-related proteins (lysyl oxidase, diamine oxidase, and monoamine oxidase A and B) was performed. In metastatic breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…LOX secretion from hypoxic tumors leads to collagen cross-linking at the pre-metastatic site and increases lung metastasis in TNBC models 28 . Moreover, higher LOX expression was observed in metastatic brain tumors of breast cancer patients 57 . Furthermore, Baker et al demonstrated that LOX increases cell proliferation and invasion in colorectal cancer via Src activation 58 and enhances matrix stiffness, activates FAK, leading to invasion in vitro and metastasis in vivo in colorectal cancer 59 .…”
Section: Discussionmentioning
confidence: 95%
“…LOX secretion from hypoxic tumors leads to collagen cross-linking at the pre-metastatic site and increases lung metastasis in TNBC models 28 . Moreover, higher LOX expression was observed in metastatic brain tumors of breast cancer patients 57 . Furthermore, Baker et al demonstrated that LOX increases cell proliferation and invasion in colorectal cancer via Src activation 58 and enhances matrix stiffness, activates FAK, leading to invasion in vitro and metastasis in vivo in colorectal cancer 59 .…”
Section: Discussionmentioning
confidence: 95%
“…In cancer, enhanced Cu levels promote tumor growth and metastasis. ,, Importantly, Cu is an essential cofactor for endothelial cell proliferation, migration, and angiogenesis . In contrast to low levels of iron, Zn, and selenium, high levels of Cu in the blood and tumor tissues of cancer patients have been reported for a wide variety of malignancies. ,, Moreover, Cu levels in cancer were found to be indicative of the course of disease .…”
Section: Immunological Effects Of Specific Metal Drugsmentioning
confidence: 99%
“…MAOA is overexpressed in the transition from breast cancer bone metastatic dormancy to relapse (Lu et al, 2011) and is required for breast tumor-initiating cells (Gwynne et al, 2019) and promotes prostate cancer metastasis (Wu et al, 2017). MAOB was recognized in a gene signature that characterizes mammary stem cells (Lim et al, 2010), and its expression is a prognostic factor in breast cancer (Cha et al, 2018). In addition, as noted earlier, MAOB and ALDH genes are included in a recently described single-cell LAM core signature (Guo et al, 2020).…”
Section: Discussionmentioning
confidence: 85%